Training in Social Justice and Culture of Life: A Challenge for the University - Díaz-Gamboa, Luis Bernardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In Colombia, the high rate of homicides committed against communal social leaders, land restitution, ex-combatants, peasants, etc. (nearly 1,000 in the last 30 months) demonstrates the need to train in social justice and preservation of life as a focus on culture embedded in the most precious good of human beings, which we all must preserve. Does the current University in Colombia serve training in social justice and the culture of life? On this question, it can be affirmed that one starts from a serious problem of social exclusion, which leads to a culture of ignorance of life and change of political, social or economic power. The theoretical framework will emerge from a construction based on the experience of the Orlando Fals Borda Human Rights Observatory at UPTC. In addition, there is the controversy about the formation in values ​​and anti-values ​​in the University, for which undoubtedly the defense of inclusive social justice and life in conditions of dignity must be taken. Thus, the need to adjust curricula and content is concluded, explaining the incardination of knowledge that guides existence towards the defense of criteria of social justice, which in parallel allows building a society where the culture of life prevails and the Uplifting peace Very linked to this effort is the protection of water factories and their governance. Therefore, it is essential to know the processes that, from the Primo Levi research group, have been advanced in this regard, around the Pisba wasteland and other human and nature rights. Closely linked to this effort is the protection of water factories and their governance. Therefore, it is essential to know the processes that, from the Primo Levi research group, have been advanced in this regard, around the Pisba wasteland and other human and nature rights.